Knowledge management as a tool to support auditing in federal educational institutions - Neto, Abdo Dias da Silva; Silva, André Luis de Oliveira (Seven Editora, 2024)
This study examines a Federal Institute of Education, Science and Technology, focusing on the effects of internal and external control on managers' actions and their perception of audits. Using structured questionnaires, data were collected from key managers to assess the value of the knowledge acquired and its dissemination. The objective is to integrate various knowledge to improve performance in the face of internal and external control requirements. The results indicate that the application of knowledge management tools can improve the dynamics between managers and internal audit, promoting a more efficient and transparent administration. In addition, the survey seeks to identify best practices in the implementation of these tools, considering the specific challenges of the federal education sector. Detailed analysis of the data reveals that continuous training of managers and the creation of an organizational culture focused on knowledge sharing are crucial for the success of audits and compliance with regulations. Finally, the study proposes recommendations to improve knowledge management policies in federal educational institutions. DOI:https://doi.org/10.56238/sevened2024.018-067